MILLENNIALS AND TAKAFUL: INVESTIGATING PURCHASE INTENTION THROUGH EXTENDED THEORY OF PLANNED BEHAVIOR AND MULTI-GROUP ANALYSIS - Fadlilah, Fajriyani Nur; Zulaikha, Siti; Zubaid, Nanda Lismatiara; Timur, Yan Putra (Jurnal Ekonomi dan Bisnis Airlangga, 2025)
Introduction: This study aims to examine the mediating role of trust between religiosity and purchase intention, as well as to assess the influence of attitude, subjective norms, perceived behavioral control (PBC), and relative advantage using an extended Theory of Planned Behaviour (TPB) framework. Methods: The PLS-SEM Multi Group Analysis approach was used as an evaluation model in the quantitative methodology using SmartPLS 4.0. Data were collected using a purposive sampling technique from Muslim respondents who are insurance customers who are millennial generation, which were then divided by gender. Results: The results show that RG, RA, SN, and PBC significantly influence ATT and TR, which in turn affect INT. All variables are key drivers of takaful adoption. Multi-Group Analysis (MGA) reveals no significant gender differences, suggesting similar behavioral patterns. Conclusion and suggestion: The strong influence of RG, RA, and TR on millennials’ ATT and INT suggests that takaful promotions should stress Islamic values, ethical benefits, and transparency. As ATT and TR directly drive INT, providers should build trust through education, digital openness, and Sharia oversight. Emphasizing social-spiritual values like ta’awun can enhance acceptance. MGA results show no gender-based differences, supporting inclusive, cost-efficient strategies to boost financial literacy and participation in Islamic finance.